Pressure-induced unfolding of L1 lipase using molecular dynamics simulations and quantum mechanics calculations - Lim, Wui Zhuan (2016)
The L1 lipase derived from Bacillus stearothermophilus is one of the most applied enzymes that shows thermostability at 333-338K and pH 8-10. It has a tetrahedral zincbinding site, which consists of Asp61, Asp238 from the core domain and His81, His87 from the extra domain of enzyme. L1 lipase is widely used as flavouring agent and aroma constituent in food industry due to its high substrate solubility and increased rate of reactions in the hydrolysis of fats and oils. Major works from X-ray crystallography and nuclear magnetic resonance (NMR) experiments have successfully deciphered the structures of known enzymes, however their dynamics and flexibility foundations are still unclear. The use of pressure can monitor protein structure and its functionality in slower kinetics, compared to temperature. Most importantly, pressure is used in food processing industries to retain vitamin and nutritional contents, and reduce the viability of microorganisms. Molecular dynamics (MD) simulations provide complementary data and valuable information to study the behaviour of macromolecules which are mostly inaccessible to experiments. From a comprehensive literature review, there is a lack of understanding on how thermoalkalophilic enzymes can unfold at high pressure, therefore 1 μs MD simulations were carried out at room temperature, to investigate the effects of 10,000 bar pressure on the structure, dynamics, and flexibility of L1 lipase. Quantum mechanics calculations were also performed by using ONIOM layer optimization to estimate the effect of high pressure on the zinc-binding site. Based on the root-mean-square deviation (RMSD) variance at 10,000 bar, small structural changes were detected. An “unfolding-up-on-squeezing” phenomenon was clearly found as the radius of gyration (Rg) was increasing gradually despite the high compression. Our solvent accessible surface area (SASA) results also illustrated the weakening of hydrophobic forces as the pressure increased. The exposure of apolar residues to water molecules allowed the greater distribution of hydrogen bonds between lipase and water molecules. In addition, the high desolvation energy correlated well with the changes in SASA values. Root-mean-square fluctuation (RMSF) analysis showed that residues 75-93, 129-145 and 283-313 were highly mobile under high pressure. The flexibility at residues 75-93 was linked to the loss of tetrahedral coordination at the zinc-binding site where His81 and His87 were involved. In terms of the secondary structures, many helix-turn transitions were observed after 400 ns of simulation. Random coil was dominant at residues 265-320. There was also an indication of beta-aggregation as the beta sheets were affected by high pressure in a lesser extent, compared to helices. Based on QM analysis, interaction at the zinc-binding site of L1 lipase was unfavourable at 10,000 bar. A lower entropy and higher enthalpy of the model system were detected. The orbital occupancy of 2pz orbital of N in His81 was decreased after bound to Zn2+ ion at high pressure. The dipole moments were also weaker for Asp61, His81 and His87. Overall, a complete unfolding of L1 lipase was not observed at 10,000 bar at 1 μs, but the obtained results revealed the formation of molten globule. This structure is possibly the universal folding intermediate because it is loosely packed and its structural features slightly resemble the native state of a folded protein. Therefore, it is very important in folding/unfolding pathway of enzyme.